2020
DOI: 10.1002/jcu.22875
|View full text |Cite
|
Sign up to set email alerts
|

Normal reference values of three‐dimensional speckle‐tracking echocardiography‐derived mitral annular dimensions and functional properties in healthy adults: Insights from the MAGYAR‐Healthy Study

Abstract: Introduction There is a limited number of echocardiographic studies determining mitral annular (MA) dimensions in healthy subjects. The present study aimed to establish normal reference values of three‐dimensional speckle‐tracking echocardiography‐derived MA dimensions and functional properties in healthy adults in relation with age and gender. Methods The present study comprised 298 healthy adult subjects. From this population, 94 subjects were excluded due to inadequate image quality. Therefore the remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In dTGA, dilated end-systolic and end-diastolic TA was found which was associated with deteriorated TA functional properties regardless of the atrial switch procedure performed ( 17 ). With known 3DSTE-derived normal reference values, in the present study, similar findings could be demonstrated for MA with dilated MA dimensions, which were associated with its impaired function ( 24 ). Senning-procedure showed (non-significant) beneficial findings during long-term (almost 30 years) follow-up.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In dTGA, dilated end-systolic and end-diastolic TA was found which was associated with deteriorated TA functional properties regardless of the atrial switch procedure performed ( 17 ). With known 3DSTE-derived normal reference values, in the present study, similar findings could be demonstrated for MA with dilated MA dimensions, which were associated with its impaired function ( 24 ). Senning-procedure showed (non-significant) beneficial findings during long-term (almost 30 years) follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…However, inter-and intraobserver variability data for MA parameters are given.  There are limited information about 3DSTE-derived MA dimensions and functional properties, but their normal reference values together with their age-and gender-dependency has just been published (24).…”
Section: Limitation Sectionmentioning
confidence: 99%
“…Although end-diastolic MA and TA diameters did not show significant change with age (decades), continuous tendentious reduction could be demonstrated in TA area and perimeter, while MA area and perimeter showed an increase-decrease pattern. While dilated end-systolic MA dimensions could be detected in ≥50 year-old subjects compared to 18-29 yearold subjects, end-systolic TA dimensions did not change with age (decades) (14). Both MAFAC and TAFAC showed reduction in older subjects compared to younger subjects.…”
Section: Reproducibility Of 3dste-derived Ta Measurementsmentioning
confidence: 74%
“…3DSTE is using a block-matching algorithm and merges advantages of 3D echocardiography (visualizing the heart as a 3D organ) and speckletracking echocardiography (quantitative featuring of wall contractility by strain and rotational parameters), and became clinically available in the early 2000s (1)(2)(3)(4). Recently, normal reference values of 3DSTE-derived left ventricular (LV) (7)(8)(9), left atrial (LA) (10,11) and right atrial (RA) (12,13) and mitral annular (MA) (14) dimensions and functional properties were determined in the MAGYAR-Healthy Study (3).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies have shown that the strain index of 3D-STE can accurately evaluate the cardiac structure and function, and the overall area strain value is highly correlated with the severity of heart failure patients, which is one of the important indicators to evaluate the left ventricular systolic function of patients. 7,8 In addition, Shin et al have recently confirmed that three-dimensional strain value has a certain correlation with left ventricular end-diastolic pressure (LVEDP) of patients with coronary heart disease, which has certain reference value for evaluating left ventricular diastolic function of patients, however, this study did not cover CHD patients with different degrees of left ventricular diastolic dysfunction due to a small number of cases and a large number of diseases. 9,10…”
Section: Introductionmentioning
confidence: 88%